Remittances, migration and Caribbean development (2007)
Examines the significance of remittances to Caribbean economies and how securitization can help to develop the market for remittances. Looks at the emerging role of diaspora home-town associations and examines approaches to utilising the skills of the diaspora in development.
Keywords: REMITTANCES